Penguatan Peran Warga sebagai Subyek Hukum dalam Penegakan Hukum Lingkungan: Studi: Partisipasi Masyarakat di Kawasan Pemukinan RT 008 RW 004, Kelurahan Malaka Jaya - Moch Fajar Yusrivandana (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyse the role of citizens as subjects of environmental law in environmental management in densely populated areas, particularly in RT 008 RW 004, Malaka Jaya Village, East Jakarta. It employs a qualitative legal method with a socio-legal approach. The results show that citizens no longer act merely as policy objects but have transformed into active legal subjects through various community-based programs. However, challenges remain, including low environmental legal literacy, limited access to information and insufficient policy and budgetary support. Therefore, stronger synergy among government, communities and other stakeholders is required to achieve sustainable environmental management.